Radio Review: Arnaud Contreras, "L'Air rebelle" (The Air of Rebellion). (26th March 2018) - Mullen, John
Abstract : L'Air rebelle: The Air of Rebellion Radio series by Arnaud Contreras on France Culture Reviewed by John Mullen, Université de Rouen, research team ERIAC